MODERN PATHOGENETIC MECHANISMS OF PERINATAL LESIONS OF THE CENTRAL NERVOUS SYSTEM IN NEWBORNS - Rustamov Bakhtiyor Bobokulovich (Scholar Express Journals, 2022)
The review article presents modern data of foreign authors on the pathogenetic aspects of the formation of perinatal lesions of the central nervous system in newborns. The author systematized medical, social and metabolic factors that are of significant importance in the development of pathology
Keywords: Newborns; Perinatal Damage Of The Central Nervous System; Encephalopathy